Game Engklek Kolam Maut Berbasis Android - M Ghofar Rohman; Arif Irawan; Masruroh Masruroh (Universitas Islam Lamongan, 2017)
The development of information technology is growing very rapidly so it can meet a variety of activities and human needs. Android is able to provide the effectiveness of the good life for humans. In addition to the Android, someone is able to create something useful. Android is now becoming a very popular program in the world has many advantages. The programs in Android provide a variety of interesting applications for learning, education, social media, games, information and so forth. Traditional games themselves are often called folk games this is a game that has been around since the days of our ancestors, which then passed down from generation to generation, like the traditional game of “Engklek” that often played by the children in rural areas. In line with the developments of science and technology traditional game is successfully combined with games thst appear on Takeshi Castle which is death pool, and also can be played on smartphones, especially with Android system, so it will be very easy to play anytime and anywhere.